2017
DOI: 10.29063/ajrh2017/v21i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Modern Contraceptive Uptake among Nigerian Women: Evidence from the National Demographic and Health Survey

Abstract: Family planning is a key strategy in the control of fertility among women. This study sought to determine various factors that influence modern family planning use in Nigeria. The study used data from Nigeria Demographic and Health Survey (NDHS) 2013. Analysis was carried out using Stata version 12.1. Multivariate logistic regression was used to determine association between various factors and use of modern family planning methods. A total of 119,386 women aged 15-49 years participated in the study. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 16 publications
9
35
4
Order By: Relevance
“…A signi cant segment identi ed as Hausa or Fulani, 50.8% and 10.2% respectively, future studies should examine how Muslim men who are Fulani or Hausa perceive contraceptive use in order to create men centric contraceptive interventions. Similar to other research, this study found a strong association between educational levels, wealth, literacy and both intention to and actual contraception use [3], [5], [10]. Living in rural areas was associated with a decreased likelihood to use contraception.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A signi cant segment identi ed as Hausa or Fulani, 50.8% and 10.2% respectively, future studies should examine how Muslim men who are Fulani or Hausa perceive contraceptive use in order to create men centric contraceptive interventions. Similar to other research, this study found a strong association between educational levels, wealth, literacy and both intention to and actual contraception use [3], [5], [10]. Living in rural areas was associated with a decreased likelihood to use contraception.…”
Section: Discussionsupporting
confidence: 89%
“…Speci cally, framing contraception not as a way to limit the number of children you can have but rather as choosing when to have children. Since Nigeria has one of the one of the highest global burdens of maternal mortality, low contraceptive use, and a high desire for more children, choosing when to have children and proper spacing can help reduce birth complications that lead to death [1], [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The women who belonged to households in the highest wealth quintile were less likely to use LARC compared to women who belonged to the lowest wealth quintile. The study contradicts ndings in Nepal, Ethiopia, Iran and Nigeria [18,42,46,47], as these studies found a positive association between LARC use with higher wealth quintile.…”
Section: Bivariate Analysiscontrasting
confidence: 84%
“…In this context, non-use of FP methods remains the main factor that favours unwanted pregnancies [11]. Several studies have reported associations between FP use and sociodemographic characteristics of women such as educational levels and socio-economic status [12][13][14][15][16][17]. Other studies indicated that the reasons for the non-use of FP include male partner disapproval of contraception, misconceptions of contraceptive side effects, di culties in accessing the FP method, and the desire to have a child [11,12,16,18].…”
Section: Introductionmentioning
confidence: 99%